RANCANG BANGUN SISTEM INFORMASI UNTUK MANAJEMEN AIR DAN PENDETEKSI KEBOCORAN PADA RUMAH INDEKOS BERBASIS INTERNET OF THINGS - Sihombing, Eka Elisa; Leslie Widjaja, Sharon; Raka Agung, I Gusti Agung Putu; Khrisne, Duman Care; Maharta Pemayun, Anak Agung Gede (Jurnal SPEKTRUM, 2025)
This study develops an IoT-based water management and leakage detection system for boarding houses to improve water usage efficiency and reduce consumption costs. The system uses an ESP32 as the main control unit, with a YF-S201 sensor to measure water flow, an HC-SR04 sensor and a water level sensor to detect water levels, and a solenoid valve to control water flow. Sensor data is sent to Firebase Realtime Database and displayed through a Laravel-based web application, allowing boarding house owners and tenants to monitor water consumption and receive automatic notifications in case of leaks. Testing results show that the system can record water consumption with an accuracy of over 95% and a precision of less than 2%, detect pipe leaks, and optimize water distribution. Additionally, the website provides features for monitoring water consumption, usage history, and water flow control. These results indicate that the IoT-based water management and leakage detection system can address water management issues in boarding houses and similar residences.